Deciphering the SNP variations linked to female sterility in Dura fruit form of oil palm: Deciphering the SNP variations linked to female sterility in Dura fruit form of oil palm - B KALYANA BABU,; P ANITHA,; R K MATHUR,; G RAVICHANDRAN,; H P BHAGYA, (Journal of Oilseeds Research, 2023)
Among the vegetable oils, palm oil which is obtained from African oil palm (Elaeisguineensis Jacq.) contributes a major share at the global oil trading centres. Taxonomically, oil palm belongs to the family Aricaceae (formerly known as Palmaceae), sub-family Arecoideae and the genus Elaeis. One breeding cycle of oil palm takes 15-18 years with lot of techniques involved in achieving good yield and oil quality of oil palm in a sustainable manner. Oil palm is a highly heterozygous and heterogeneous crop with high diversity in the germplasm (Babu et al. 2020). Oil palm can be divided into mainly three forms based on the shell thickness of the fruits i.e., dura, pisifera, and tenera, whereas another type of fruit form called macrocarya also exists but not common. Based on fruit color, oil palm is classified into two types i.e., Virescence and Nigrescence type. Nigrescence is the commonly found fruit color among the commercially grown oil palm farms. In terms of quality, palm oil has approximately equal distribution of saturated to unsaturated fatty acids (UFAs). Most of the oil palm breeding programmes in generating high yielding varieties were restricted to dura variety which is having thick shelled fruit form till the 1950s. Later, research efforts at some countries like Africa, Malaysia and Indonesia resulted in generation of various breeding populations originated from the four Bogorpalms and their progenies.